The Influence of Carbon Tax on the Feasibility of Industrial Project: A Case Study of Heat Exchanger Replacement at PT Kaltim Methanol Industri, Indonesia - Dewanatan, Wingo Wira; Adiputra, Muhammad Kurniawan; Putro, Imam Karfendi; Hartanto, Soni; Kristanto, Jonas; Azis, Muhammad Mufti (ASEAN Journal of Chemical Engineering, 2020)
Petrochemical industries have faced growing pressure to decrease their carbon emission from direct and indirect sources. This work aims to demonstrate a carbon tax’s introduction to a feasibility study on the heat exchanger (HE) replacement project at PT Kaltim Methanol Industri, Indonesia. The project was aimed to avoid methanol release as much as 48.88 MT/year. The release of methanol can also be associated with CO2 emission with an emission factor of 0.6 ton CO2e/ton methanol. Here, we investigated the influence of inclusion and exclusion of carbon tax to monetize the CO2 release. From the project investment point of view, carbon tax inclusion is expected to increase the cost-saving. Introduction of the carbon tax as high as 10 USD/ton CO2e with 5% annual increase gives IRR value of 7.06% with Payout Time (PoT) of ca. 11 years. The IRR value without carbon tax scenario is 6.68 % with the same range of PoT. Hence, the inclusion of carbon tax may increase the feasibility of the project. This work has demonstrated the positive role of the carbon tax to increase the feasibility of a project which inlines with the national initiatives to curb the CO2 emission from chemical industries. It is also worth noting that introduction of carbon tax should be accompanied by a reorganization of government incentives, including several financial policies to create a conducive atmosphere for investors in Indonesia.